Impact of COVID-19 on Healthcare Resource Utilisation Among Patients with Inflammatory Bowel Disease in the USA. (9th April 2022) - Ungaro, Ryan C; Chou, Bonnie; Mo, Jason; Ursos, Lyann; Twardowski, Rachel; Candela, Ninfa; Colombel, Jean-Frederic
Abstract: Background and Aims: The impact of the COVID-19 pandemic on patients with inflammatory bowel disease [IBD] is largely unknown. We characterised the impact of COVID-19 on IBD care by conducting an analysis of US health care claims data. Methods: We obtained de-identified, open-source, health insurance claims data, from January 2019 to December 2020, from the Symphony Health Integrated Dataverse for US adults with IBD, and measured the rates per 1000 patients of five outcomes: colonoscopies; new biologic or small molecule treatment initiations or treatment switches; new biologic or small molecule treatment initiations or treatment switches in patients who had a colonoscopy within the previous 60 days; IBD-related surgeries; and telehealth consultations. Results: For 2019 and 2020, 1.32 million and 1.29 million patients with IBD, respectively, were included in the analysis. In March–April 2020, the rates of colonoscopies [17.39 vs 34.44], new biologic or small molecule treatment initiations or switches in patients who had a colonoscopy within the previous 60 days [0.76 vs 1.18], and IBD-related surgeries [2.33 vs 2.99] per 1000 patients were significantly decreased versus January–February 2020; significant year on year decreases versus 2019 were also observed. Telehealth utilisation increased in March 2020 and remained higher than in 2019 up to December 2020. Conclusions: Reduction in colonoscopies and subsequent initiation/switching of treatments during the COVID-19 pandemic suggest lost opportunities for therapy optimisation which may have an impact on longer-term patient outcomes. Increased utilisation of telehealth services may have helped address gaps in routine clinical care. Graphical Abstract: